(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2011)
Background: Variation in tooth size is influenced by genetic and environmental factors. Several studies have reported tooth size variation between and within different racial groups. In order to improve the quality of dental care available, there is a great need for data on the mesiodistal crown dimensions of the individual teeth of Bangladeshi population. Objectives: To find nominative data on the mesiodistal crown dimensions of permanent teeth in Bangladeshi population and to compare the findings with those reported in other populations. Methods: This observational study was done from January, 2008 to June, 2010 in the Department of Orthodontics, Faculty of Dentistry, Bangabandhu Sheikh Mujib Medical University. A total of 244 Bangladeshi subjects (77 males and 167 females), aged 7 – 36 years (mean 18.3 years) with no age limit who attended at the above mentioned place for treatment were included in the study. Main outcome measure was mesiodistal crown dimension of each tooth class of permanent dentition. Mesiodistal crown dimensions were measured from dental casts of the permanent teeth. Results: Males had significantly larger teeth than females for maxillary central incisors (p < 0.05) and for the mandibular second premolars (p < 0.001). In both sexes, the maxillary lateral incisors showed the greatest variability [coefficient of variation (CV) 10.7%] and the maxillary canines the least (CV 6.9%) in mesiodistal crown dimension. Mandibular canines displayed greater sexual dimorphism in mesiodistal crown size than in any other tooth classes. Comparisons of the mesiodistal crown dimensions between population groups showed that Bangladeshis have tooth sizes close to those of North Indians, Icelanders and Jordanians but larger than those of North American Whites. Conclusions: From this study, a standard for the mesiodistal crown dimensions of permanent dentition of Bangladeshi males and females are obtained. Key Words: Crown dimension; Mesio-Distal width; Permanent dentition. DOI: http://dx.doi.org/10.3329/bsmmuj.v4i2.8635 BSMMU J 2011; 4(2):81-87